The onset of star formation 250 million years after the Big Bang - Hashimoto, Takuya; Rydberg, Claes-Erik (Nature, 2018)
Observation of the emission line of doubly ionized oxygen at a redshift of 9.1096 reveals that star formation began at a redshift of about 15, around 250 million years after the Big Bang.
Gesehen am 16.10.2019